OPTIMASI MORINGA GUM DAN POLIVINIL ALKOHOL DALAM SEDIAAN MUCOADHESIVE BUCCAL FILM DILTIAZEM HIDROKLORIDA - Nani Sukmawati; Lusia Oktora Ruma Kumala Sari; Eka Deddy Irawan (Jurnal Kesehatan Islam : Islamic Health Journal, 2024)
Abstract. Diltiazem Hydrochloride (HCl) is commonly used in hypertension therapy for its beneficial effects, such as reducing blood vessel pressure resistance and relaxing the heart muscles. In an in-vivo study, Diltiazem HCl is known to be decrease by 60% of its bioavailability due to first-pass metabolism. Thus, it is necessary to develop a new administration route, some of which is buccal drug delivery route in mucoadhesive buccal film. Moringa gum is a polyuronide polymer with a hydroxyl group in its side chains, giving the potential use as a mucoadhesive polymer. However, it has poor folding endurance and its release kinetics study has not been investigated. Polyvinyl alcohol (PVA) is a water-soluble polymer with hydroxyl side chain. PVA is known for its high tensile strength and flexibility, though it can be affected by humidity. The aim of this research is to determine the right amount of moringa gum and PVA to obtain a film with good physical characteristics and mucoadhesive residence time. In this study, the optimization of moringa gum and PVA was carried out using factorial design. Mucoadhesive buccal film was prepared by solvent casting method, the films were later evaluated and the obtained responses were analyzed by Software Design Expert 11.0.0. The optimization result shows the film containing the amount of moringa gum 2% and PVA 5% can produce the optimum formula. The mucoadhesive buccal film formula has surface pH of 6.083, mucoadhesive residence time of 445.055 min, swelling index of 4.067, and 87.9913% drug release in in-vitro drug release study after 420 min following the Higuchi model release kinetics. Therefore, it can be concluded that the obtained optimum formula of mucoadhesive buccal film can be used in the preparation of mucoadhesive buccal film Diltiazem HCl.. Kata Kunci: Hypertension; Diltiazem HCl; Mucoadhesive buccal film; Moringa gum; PVA.